Drawing In and Fading Out: The case of the Commonwealth Games Housing Village, Western Australia - Lewi, H.; Neille, Stephen (Blackwell Synergy, 2007)
The collection of 150 modern houses that comprised the Athletes' Village for the event of the VIIth Commonwealth Games in Perth, Western Australia, in 1962, is now rapidly disappearing. This fading out is in part due to the changing expectations of suburban house design in Australia today and, in part, due to the inevitable aging of the garden suburb in which these houses are located. Moreover, its demise has been precipitated by a recent failed effort to conserve and protect the development by the Heritage Council of Western Australia. This article addresses the history of the Athlete's Village, demonstrates its architectural and historical significance, the changes that have occurred in it over time, the author's documentation of those changes, and why we believe that heritage designation and protection proposals for the site were not supported.